RANGKUMAN dan pengayaan Ilmu Pengetahuan Alam : Kelas 1 SD semester 1 / Monica Chandra Wahyu...[et al] ; editor, Y. Hery Kurniyanta, F.A. Dimas Andika W, Olivia Dewi Maharani ; ilustrator, Harnawan - Monica Chandra Wahyu; Hery Kurniyanta, Y.; Dimas Andika W, F.A.; Olivia Dewi Maharani (Kanisius, 2016)
128 hlm. : ilus. ; 25 cm